设 $\boldsymbol{A}, \boldsymbol{B}$ 都是 3 阶矩阵, 存在可逆矩阵 $\boldsymbol{P}$, 使 $\boldsymbol{A P}=\boldsymbol{P B}$, 且 $\boldsymbol{A}$ 满足 $\boldsymbol{A}^2-\boldsymbol{A}-2 \boldsymbol{E}=\boldsymbol{O},|\boldsymbol{A}|+1 < $ 0 , 则 $\left|(3 \boldsymbol{B})^{-1}-\left(\frac{1}{2} \boldsymbol{B}\right)^{\cdot}\right|=$
【答案】 $-\frac{16}{27}$.


【解析】 设 $\lambda$ 是 $\boldsymbol{A}$ 的任一特征值, 则由 $\boldsymbol{A}^2-\boldsymbol{A}-2 \boldsymbol{E}=\boldsymbol{O}$, 得 $\lambda^2-\lambda-2=0$, 故 $\boldsymbol{A}$ 的特征值是 $-1$ 或 2 , 再由 $|\boldsymbol{A}|+1 < 0$, 得 $\boldsymbol{A}$ 的特征值为 $-1,2,2$.
由 $A P=P B$, 得 $B=P^{-1} A P, A, B$ 相似, 故 $B$ 的特征值为 $-1,2,2$, 于是
$$
|\boldsymbol{B}|=-4,\left(\frac{1}{2} \boldsymbol{B}\right)^{\cdot}=\left(\frac{1}{2}\right)^2 \boldsymbol{B}^{\cdot}=\frac{1}{4}|\boldsymbol{B}| \boldsymbol{B}^{-1}=-\boldsymbol{B}^{-1},
$$
因此, $\left|(3 \boldsymbol{B})^{-1}-\left(\frac{1}{2} \boldsymbol{B}\right)^{\cdot}\right|=\left|\frac{1}{3} \boldsymbol{B}^{-1}+\boldsymbol{B}^{-1}\right|=\left|\frac{4}{3} \boldsymbol{B}^{-1}\right|=\left(\frac{4}{3}\right)^3 \frac{1}{|\boldsymbol{B}|}=-\frac{16}{27}$.
系统推荐